Fighting Crime Across Borders: Sovereign Equality and Judicial Cooperation in Criminal Matters - Wielec, Marcin (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
The article examines the role of equality as a fundamental principle in judicial cooperation within the EU, tracing its evolution and impact concerning criminal law. The discussion begins with an outline of the significance of equality in the EU’s formation and its early stages of cooperation. It explores the historical development of judicial cooperation in criminal matters, highlighting its transformation into a key element of EU integration. The analysis focuses on the principle of equality within the current framework of judicial cooperation, emphasising the adoption of common minimum standards for criminal proceedings as a basic model. These standards ensure uniformity and fairness while preserving equality among the Member States. The article delves into how these standards influence the equality of the Member States in criminal law enforcement and judicial processes. Key areas of criminal law are explored to illustrate the practical application of equality in judicial cooperation, including efforts to combat terrorism, corruption, cybercrime, fraud and money laundering, alongside measures to protect victims. The article addresses the challenges posed to equality by European integration, discussing sovereignty, the rule of law and the emerging role of the European Public Prosecutor’s Office. Additionally, it highlights the pivotal role of the Court of Justice of the European Union in upholding the principle of equality in judicial cooperation. The article concludes by summarising the complex interplay between equality, sovereignty and judicial cooperation in the EU, underscoring the continued importance of this principle in fostering integration and addressing contemporary challenges.